The Regulation between CD4+CXCR5+ Follicular Helper T (Tfh) Cells and CD19+CD24hiCD38hi Regulatory B (Breg) Cells in Gastric Cancer - Ying Zhang; Jun Wu; Haibo Zhang; Chen Wu (Journal of Immunology Research)
Purpose. T follicular helper (Tfh) cells and regulatory B (Breg) cells are reported to play essential roles in humoral immunity, especially in inflammation, autoimmune diseases, and cancer. Hence, we sought to investigate the involvement of CXCR5+CD4+ Tfh cells and CD19+CD24hiCD38hi Breg cells in gastric cancer. Methods. The blood samples were obtained from 36 gastric cancer patients and 18 healthy individuals. The percentage of Tfh cells (Tfh%) and Breg cells (Breg%) was detected via flow cytometry, while IL-21, IL-10, and CXCL13 levels were examined with ELISA. The association between them and clinical parameters of patients was also assessed. The in vitro Tfh-B cell coculture experiments were performed for six days, and then, Tfh%, Breg%, and cytokines were valued by flow cytometry and ELISA, respectively. Results. Tfh%, Breg%, and CXCL13 level were significantly increased among gastric cancer patients. Moreover, higher Tfh% was associated with lymphatic metastasis, patients’ worse outcomes and Breg%. Tfh differentiation and CXCL13 were upregulated by cocultured B cells in vitro, while Tfh cells seem to not participate in Breg cell differentiation from B cells. Conclusion. Altogether, increased Tfh and Breg cells could be involved in immune suppression in gastric cancer. Moreover, B cell may be a potential regulator for Tfh differentiation, while Tfh cells had no significant effects on the regulation of Breg cells.